Kinetics of Inhibition of Influenza Virus Hemagglutination by Homologous Antihemagglutinin and Antineuraminidase Antibodies as Measured by Means of the Photometric Antibody Concentration Unit Method - Drescher, Joachim (1974)
The kinetics of the reactions of antihemagglutinin (AH) and antineuraminidase (AN) antibodies with homologous influenza virus were examined by use of a photometric hemagglutination inhibition test (antibody concentration unit [ACU] test). The following results were obtained. (i) The isotherms describing the reaction of AN antibodies with homologous virus were found to have much steeper slopes than did the corresponding AH antibody isotherm. This finding indicates that the photometric ACU method can discriminate objectively between AH and AN antibodies. (ii) The reaction of mixtures of AH and AN antibodies with homologous virus was examined and found that AH antibodies combine with virus independently from the presence of AN antibodies, whereas AH antibodies were found to reduce greatly the measurable degree of hemagglutination inhibition by AN antibodies. (iii) A formula was developed and experimentally confirmed by means of which the binding of virus by mixtures of AH and AN antibodies can be predicted. Thereby, the influence of the relative concentration of AH and AN antibodies on the establishing of isotherms and on their subsequent use for antibody titration by means of the photometric ACU method was investigated. It was found that the procedure routinely employed for establishing isotherms yielded data reflecting the reaction of AH antibodies only. As a consequence, the use of these isotherms will identify AH antibodies.